2015
DOI: 10.3109/16066359.2015.1093122
|View full text |Cite
|
Sign up to set email alerts
|

Occupational inequalities in psychoactive substance use: A question of conceptualization?

Abstract: Background: Three different conceptualizations of occupational prestige were contrasted by applying social stratification to four exemplarily selected psychoactive substances. Although these conceptualizations partly measure the same construct, it is hypothesized that the gradient of occupational inequality differs depending on the type of conceptualization. Method: Data were taken from the 2012 German Epidemiological Survey of Substance Abuse. The study sample comprised n ¼ 9084 individuals of the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
9
0
2
Order By: Relevance
“…In these cases, SES effects—positive as well as negative ones—were greatest in countries of low GDP or high‐income inequality. The finding that socioeconomic disparities vary in direction depending on the SES indicator as well as the specific outcome is corroborated by previous research . The simultaneous use of different individual‐level SES indicators revealed opposite effects on drinking for different indicators.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In these cases, SES effects—positive as well as negative ones—were greatest in countries of low GDP or high‐income inequality. The finding that socioeconomic disparities vary in direction depending on the SES indicator as well as the specific outcome is corroborated by previous research . The simultaneous use of different individual‐level SES indicators revealed opposite effects on drinking for different indicators.…”
Section: Discussionsupporting
confidence: 80%
“…Socioeconomic disparities in alcohol use describe differences in alcohol consumption by individuals in different social and economic situations, that is, their socioeconomic status (SES) . Common indicators of SES are education, income/wealth and occupational prestige, which describe different aspects of SES . Thus, educational disparities, for example, can be regarded as one specific kind of socioeconomic disparity.…”
Section: Introductionmentioning
confidence: 99%
“… High-Income ( Hwang and Lee, 2014 ) Cancer Longitudinal Highest level of education, highest level of education (household), EPG score: last profession, U&S score: last profession Breast Cancer Blue-collar women vs. other women There was no difference in breast cancer risk in blue-collar women and lower white-collar women (RR = 1.01, 95% CI 0.69–1.49); the risk of breast cancer was increased among upper white-collar women as compared with blue-collar women (RR = 1.19, 95% CI 0.80 –1.76). The Netherlands Cohort Study (NLCS) High-Income ( Van Loon et al, 1994 ) Longitudinal Highest level of education, occupational class, social standing (U&S) score Colon Cancer Blue-collar women vs. other women As compared with blue-collar women, the risk of colon cancer was increased among lower white-collar women (RR = 1.30, 95% CI 0.76–2.22) but decreased among upper white-collar women (RR = 0.63, 95% CI 0.30–1.29) The Netherlands Cohort Study (NLCS) High-Income ( Van Loon et al, 1995 ) Case-Control Occupation Cancer of the CNS Blue-collar women vs. other women Industries showing consistent increases in risk for cancer of the CNS by gender and race included textile mills, paper mills, printing and publishing industries, petroleum refining, motor vehicles manufacturing, telephone and electric utilities, department stores, health care services, elementary and secondary schools, and colleges and universities. United States Vital Statistics Records High-Income ( Cocco et al, 1999 ) Longitudinal Occupation Breast Cancer Blue-collar women vs. other women Excess risk for breast cancer was found for pharmacists, teachers of theoretical subjects, schoolmasters, systems analysts and programmers, telephone operators, telegraph and radio operators, metal platers and coaters, and hairdressers and beauticians.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of breast cancer risk in blue-collar women versus women in other industries and job types yielded mixed findings. While one study from the Netherlands found no difference in breast cancer risk in blue- and white-collar women, results from a Swedish case-control study suggest excess breast cancer risk among metal platers and coaters and results from a longitudinal U.S. study suggest increased breast cancer risk in female crafts/operatives as compared with housewives ( Maron et al, 2016 , Mattioli et al, 2009 , Mattisson et al, 2014 ). However, studies suggest decreased risk for lung cancer and colon cancer in blue- versus white-collar women ( Maty et al, 2005 , McCormack et al, 2006 ).…”
Section: Description Of Findings By Health Outcome Categorymentioning
confidence: 94%
“…Studies show that, in most cases, consumption remains experimental or occasional . The vast majority of current users are aged less than 34 years and are concentrated in the less affluent social groups, unemployed and less educated . Recently, it has been found that the pattern of cannabis consumption by adolescents depends largely upon their social background: not only do adolescents from affluent families experiment or smoke less frequently, but the proportions of regular, intensive or problematic users are also lower in this group than among adolescents from more modest backgrounds .…”
Section: Introductionmentioning
confidence: 99%